Single-center experience of liver transplantation for perihilar cholangiocarcinoma. Issue 4 (April 2022) - Ahmed, Ola; Vachharajani, Neeta; Chang, Su-Hsin; Park, Yikyung; Khan, Adeel S.; Chapman, William C.; Doyle, M.B.M.
Abstract: Background: Traditionally, curative resection was considered the cornerstone of treatment for perihilar cholangiocarcinoma. More recently, liver transplantation (LT) offered an alternative for patients with unresectable disease. The purpose of this study was to assess our experience with perihilar cholangiocarcinoma and LT. Methods: A perihilar cholangiocarcinoma protocol was commenced in 2006 whereby diagnosed patients were enrolled onto an institutional registry for LT consideration. Data on patient progression and oncologic outcomes were assessed. Results: Fifty-eight patients were initially enrolled onto the protocol and 38 proceeded to LT following neoadjuvant chemoradiation (mean age 55.6 ± 11.4 years). Mean time to LT was 3.7 ± 2 months and, among those transplanted, 14 (37%) had underlying primary sclerosing cholangitis (PSC). Thirteen (34%) patients developed malignant recurrence and there were no differences in disease recurrence between PSC (n = 3) and non-PSC (n = 10) patients (p = 0.32). Overall patient survival was 91%, 58% and 52% at 1-, 3- and 5-years corresponding with 81%, 52% and 46% graft survival, respectively. Conclusion: Rigorous patient selection and chemoradiation treatment algorithms can be highly effective in treating perihilar cholangiocarcinoma. For appropriately selected candidates, LT can provide a 52% 5-year survival for patients who would otherwise have no surgical treatment option.